2016
DOI: 10.1073/pnas.1608795113
|View full text |Cite
|
Sign up to set email alerts
|

Htm1p–Pdi1p is a folding-sensitive mannosidase that marks N-glycoproteins for ER-associated protein degradation

Abstract: Our understanding of how the endoplasmic reticulum (ER)-associated protein degradation (ERAD) machinery efficiently targets terminally misfolded proteins while avoiding the misidentification of nascent polypeptides and correctly folded proteins is limited. For luminal N-glycoproteins, demannosylation of their N-glycan to expose a terminal α1,6-linked mannose is necessary for their degradation via ERAD, but whether this modification is specific to misfolded proteins is unknown. Here we report that the complex o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…They uncovered that EBS7 (methanesulfonate-mutagenized brassinosteroid insensitive 1 suppressor 7) interacts with the ER membrane-anchored ubiquitin ligase AtHrd1a, one of the central components of the Arabidopsis ERAD machinery, whose mutation destabilizes AtHrd1a to reduce polyubiquitination. Similarly, very recently, Liu et al ( 2016 ) demonstrated that α1, 6-linked mannose is necessary for luminal N-glycoproteins degradation via ERAD system in yeast where Htm1p-Pdi1p complex acts as a folding-sensitive mannosidase for catalyzing the first committed step. Thus, any defects in this sophisticated ERAD machinery system raise death and life issues of cells survival, especially under stressed environments.…”
Section: Repairing Of Damaged Proteinsmentioning
confidence: 83%
“…They uncovered that EBS7 (methanesulfonate-mutagenized brassinosteroid insensitive 1 suppressor 7) interacts with the ER membrane-anchored ubiquitin ligase AtHrd1a, one of the central components of the Arabidopsis ERAD machinery, whose mutation destabilizes AtHrd1a to reduce polyubiquitination. Similarly, very recently, Liu et al ( 2016 ) demonstrated that α1, 6-linked mannose is necessary for luminal N-glycoproteins degradation via ERAD system in yeast where Htm1p-Pdi1p complex acts as a folding-sensitive mannosidase for catalyzing the first committed step. Thus, any defects in this sophisticated ERAD machinery system raise death and life issues of cells survival, especially under stressed environments.…”
Section: Repairing Of Damaged Proteinsmentioning
confidence: 83%
“…As the S. cerevisiae EDEM homolog Htm1p was shown to associate with PDI to produce a functional mannosidase 19 , 21 , 22 , we tested whether mammalian PDI would increase the activity of EDEM1. Indeed, we could see an increase in trimming, although modest, when EDEM1 was in the presence of PDI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with those found for the S. cerevisiae EDEM homolog Htm1. Htm1 forms a complex with PDI, with a modest mannosidase activity and a preference for misfolded or partially unfolded glycoprotein substrates 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of them appear to contain folding sensing properties directly or through their associated co-factors. Htm1p mannosidase activity is aided by an associated oxidoreductase, Pdi1p [127,128]. While EDEM1 appears to stably bind ERAD substrates independently of its associated factors BiP and ERdj5, its binding appears to be bi-partite in that it has a stable interaction that survives harsh treatments that is thiol dependent and likely covalent, as well as a weaker interaction with substrates that is thiol independent [122,129].…”
Section: Carbohydrate-dependent Protein Quality Controlmentioning
confidence: 99%